2007
DOI: 10.1007/s11292-007-9031-3
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between judges and the public? A multi-method study

Abstract: This article examines the gap between Dutch judges and the public in terms of preferred severity of sentences. It focuses on one particular explanation usually given for the gap: the lack of case-specific, detailed information on the part of the general public. Findings from three studies are reported and combined: (a) a survey among a sample from the Dutch population (N=2,127), (b) a sentencing experiment with judges in Dutch criminal courts (N=180), and (c) a sentencing experiment, using the same case materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…Indeed, it might be the case that these differences in the limited versus full use of cognitive resources may explain why there sometimes is a discrepancy between the general public and legal professionals in justice-based responses to criminal offenders, potentially producing tension in society by means of a public desire for more severe punishment regulations (cf. De Keijser, Van Koppen, & Elffers, 2007). These latter considerations are highly speculative, of course, but they do illuminate that the processes described in the present article may be relevant to understand a variety of human reactions to perpetrators of severe crimes.…”
Section: Discussionmentioning
confidence: 74%
“…Indeed, it might be the case that these differences in the limited versus full use of cognitive resources may explain why there sometimes is a discrepancy between the general public and legal professionals in justice-based responses to criminal offenders, potentially producing tension in society by means of a public desire for more severe punishment regulations (cf. De Keijser, Van Koppen, & Elffers, 2007). These latter considerations are highly speculative, of course, but they do illuminate that the processes described in the present article may be relevant to understand a variety of human reactions to perpetrators of severe crimes.…”
Section: Discussionmentioning
confidence: 74%
“…Respondents who read newspaper accounts were significantly more punitive in their sentencing and also more likely to disapprove of the judge's decision than those who were given detailed court-based information. The essential finding -that the provision of information attenuates punitiveness and moderates criticism of sentencers -has subsequently been replicated in a range of other jurisdictions (see for example de Keijser et al (2007) in the Netherlands and Warner and Davis (2012) in Australia b , ).…”
Section: Introductionmentioning
confidence: 95%
“…Experimental studies designed to unpick the relationships between knowledge and punitivity have suggested that less punitive attitudes are uncovered when methodologies are used that allow the provision of information and deliberation (Doob and Roberts 1998;Chapman, Mirrlees-Black and Brown 2002;Indermaur and Hough 2002;Hough and Park 2002;Luskin, Fishkin and Jowell 2002;Hutton 2005;Keijser, Koppen and Elffers 2007;Warner and Davis 2012).…”
Section: Introductionmentioning
confidence: 99%
“…de Keijser et al 2007;Oswald et al 2002;Weiner et al 1997). First, based on the retributive justification of punishment, we discuss how society has a right and duty to punish lawbreakers to ensure that the victim of a crime receives moral restitution for the violation of his/her rights.…”
Section: Attitudes To Punishment and Knowledgementioning
confidence: 99%
“…In the literature, discussion is principally focused on how great this impact is and whether the punitive gap can be completely bridged when a sufficient amount of information is provided. For example, de Keijser et al (2007) found that very detailed information concerning a case reduced the punitive gap but was unable to eliminate it completely. Researchers who carried out a study in Switzerland noted that in verdicts given by laypeople and professional judges based on the normal vignette method, no great difference was observed.…”
Section: Sentencing Decisions and The Punitive Gapmentioning
confidence: 99%